Sikap Petani Muda Terhadap Keputusan Usahatani Padi Sawah (Oryza Sativa L) di Kecamatan Sungai Raya - Ulfika, Ulfika; Kurniati, Dewi; Maswadi, Maswadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research was carried out in Sungai Raya District, this research started from October 2022 to November 2023. The population of this research was 40 young farmers. The aim of this research is to analyze the attitudes and decisions of young farmers in choosing lowland rice farming and to analyze the relationship between the attitudes and decisions of young farmers in choosing lowland rice farming in Sungai Raya District. The method used to determine respondents with an age range of 20-40 years and still actively cultivating rice fields. Data collection techniques were carried out using interviews, questionnaires and observation. The results of the research show that the ability of young farmers to cultivate lowland rice is very optimal, seen from several indicators such as processing lowland rice farming, meeting economic needs and food needs. The relationship between young farmers' attitudes and decisions in choosing lowland rice farming is significant with a strong level of closeness and has a positive or unidirectional relationship, which means that if young farmers' attitudes are improved, young farmers' decisions in choosing lowland rice farming will also increase.